PENGARUH HARGA, KERAGAMAN PRODUK, DAN KUALITAS PELAYANAN TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL INTERVENING PADA TOKO SUMBER KEHURIPAN DI SUMBERTENGAH SITUBONDO - Siti Khumairoh; Lusiana Tulhusnah; Rini Kartika Sari (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
Marketing is a series of activities carried out by companies or individuals to introduce, offer, and distribute products or services to consumers with the main goal of fulfilling their needs and wants. The purpose of this study is to determine the effect of Price, Product Variety, and Service Quality on Consumer Loyalty with Customer Satisfaction as an Intervening Variable at Toko Sumber Kehuripan in Sumber Tengah, Situbondo. The sampling technique used in this research is purposive sampling. Data analysis and hypothesis testing were conducted using the Smart PLS 3.0 application. The results of this study show that Price has a significant positive effect on Customer Satisfaction, while Product Variety and Service Quality have a positive but not significant effect on Customer Satisfaction. Price and Product Variety have a positive but not significant effect on Consumer Loyalty, while Service Quality has a significant positive effect on Consumer Loyalty. Customer Satisfaction has a significant positive effect on Consumer Loyalty. However, Price, Product Variety, and Service Quality have a positive but not significant effect on Consumer Loyalty through Customer Satisfaction.